Dampak Penggunaan Gadget terhadap Keterlambatan Bicara Anak Usia Dini - Lina Mariani; Syamsiah Depalina (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
Language development in early childhood is a fundamental aspect in shaping children's cognitive, social, and emotional abilities. However, in today's digital era, excessive use of gadgets has become a common habit in parenting patterns, which has the potential to inhibit children's speech development. This article aims to examine the impact of gadget use on speech delays in early childhood using a literature review approach to the literature from 2020–2025. The results of the study indicate that passive interaction through gadgets, without adequate verbal guidance and stimulation, can reduce the frequency of dialogue and children's social involvement. This condition increases the risk of speech delay, expressive communication disorders, and vocabulary limitations. In addition, factors such as permissive parenting, technoference, and lack of direct verbal activity are significant contributors to obstacles to language development. Therefore, an active role is needed for parents in limiting screen time, assisting with the use of digital media, and creating an environment rich in verbal interaction. Public education and early detection are also important solutions to prevent and treat speech delays from an early age.